Demonstration of ultrasound-mediated therapeutic delivery of fibrin-targeted pioglitazone-loaded echogenic liposomes into the arterial bed for attenuation of peri-stent restenosis. (2nd January 2023) - Klegerman, Melvin E.; Moody, Melanie R.; Huang, Shao-Ling; Peng, Tao; Laing, Susan T.; Govindarajan, Vijay; Danila, Delia; Tahanan, Amirali; Rahbar, Mohammad H.; Vela, Deborah; Genstler, Curtis; Haworth, Kevin J.; et al.
Abstract: Peri-stent restenosis following stent implantation is a major clinical problem. We have previously demonstrated that ultrasound-facilitated liposomal delivery of pioglitazone (PGN) to the arterial wall attenuated in-stent restenosis. To evaluate ultrasound mediated arterial delivery, in Yucatan miniswine, balloon inflations were performed in the carotid and subclavian arteries to simulate stent implantation and induce fibrin formation. The fibrin-binding peptide, GPRPPGGGC, was conjugated to echogenic liposomes (ELIP) containing dinitrophenyl-L-alanine-labelled pioglitazone (DNP-PGN) for targeting purposes. After pre-treating the arteries with nitroglycerine, fibrin-binding peptide-conjugated PGN-loaded ELIP (PAFb-DNP-PGN-ELIP also termed atheroglitatide) were delivered to the injured arteries via an endovascular catheter with an ultrasound core, either with or without ultrasound application (EKOS TM Endovascular System, Boston Scientific). In arteries treated with atheroglitatide, there was substantial delivery of PGN into the superficial layers (5 µm from the lumen) of the arteries with and without ultrasound, [(1951.17 relative fluorescence units (RFU) vs. 1901.17 RFU; P -value = 0.939)]. With ultrasound activation there was increased penetration of PGN into the deeper arterial layers (up to 35 µm from the lumen) [(13195.25 RFU vs. 7681.00 RFU; P -value = 0.005)]. These pre-clinical data demonstrate ultrasound mediated therapeutic vascular delivery to deeper layers of the injured arterial wall. This model has the potential to reduce peri- stent restenosis.